Ecology and natural history of the Masarid wasps of the world with an assessment of their role as pollinators in southern Africa (Hymenoptera : Vespoidea : Masaridae) - Gess, Sarah Kathleen (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1993)
The worldwide knowledge of the ecology and natural history of the masarid wasps, those wasps which bee-like provision their nest cells with pollen and nectar, is synthesized and discussed putting into context the investigations concerning nesting and flower visiting by southern African masarids conducted by the present author. Masarids are found mostly to favour warm to hot areas with relatively low rainfall and open scrubby vegetation. At the generic level the masarids of the Nearctic, Neotropical and Australian regions are distinct from each other and from those of the Palaearctic and Afrotropical regions combined. No species are shared between regions. Southern Africa is apparently the area of greatest species diversity. In this region, at least, there is a high incidence of narrow endemism. Masarids are associated with a relatively small range of plant families. Where sufficient records are available distinct major preferences are shown between zoogeographical regions. Relatedness of plant preferences between zoogeographical regions is apparent when relatedness of plant taxa is considered. Within a region there is marked overlap in masarid generic preferences for flower families. At the specific level there is marked oligolecty and narrow polylecty. The majority of nesting studies indicate that nest construction, egg laying and provisioning are performed by a single female per nest, however, nest sharing has been alledged for two species. No parasitic masarids have been recorded. Egg laying precedes provisioning. Mass provisioning is the rule. According to species, nests are sited in the ground, in non-friable soil or friable soil, in earthen vertical banks, on stones or on plants. Seven nest types are defined. Three bonding agents, water, nectar and self-generated silk are used. Masarids are evaluated as potential pollinators of their forage plants in southern Africa. The "masarid pollination syndrome", though less broad is shown to fall within that designated melittophily. The case studies considered make it clear that, whereas the masarids visiting some flower groups are members of a guild of potential pollinators, the masarids visiting others are probably their most important pollinators. Increasing land utilization is shown to threaten the existence of narrowly endmic masarid species.
Keywords: Wasps -- Ecology; Pollen wasps -- Ecology; Vespidae -- Ecology; Pollination by insects -- Africa, Southern